1998
DOI: 10.1103/physrevb.57.r14020
|View full text |Cite
|
Sign up to set email alerts
|

Unusual effect of interatomic interactions on magnetism: Rh adatoms on the Ag(001) surface

Abstract: We demonstrate that there exists an anomalous increase in the magnetic moments of Rh adatoms on the Ag͑001͒ surface with decreasing interatomic distance between adatoms, whereas for dimers of other transition metals the opposite behavior is observed. First-principles calculations, based on the local approximation of the density-functional theory and the Korringa-Kohn-Rostoker Green's-function method, are performed. We discuss the reliability of a standard parametrization of a tight-binding model for the descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…et al34 for Rh nanoclusters supported on Ag͑001͒. In contrast to 3d clusters such as Ni, where we have obtained in a previous work a linear decreasing dependence of with Z ͑see Ref.…”
contrasting
confidence: 47%
See 1 more Smart Citation
“…et al34 for Rh nanoclusters supported on Ag͑001͒. In contrast to 3d clusters such as Ni, where we have obtained in a previous work a linear decreasing dependence of with Z ͑see Ref.…”
contrasting
confidence: 47%
“…In another context, ab initio calculations for the Rh dimer supported on Ag͑001͒ have also shown that this metal does not always follow the general trends of magnetism with respect to the coordination number and interatomic distances. 34 The local magnetic moment in the supported dimer decreases while increasing the interatomic distance, in contrast to the general behavior of the 3d elements. Therefore, we believe that a systematic study of both the geometrical structure and magnetic properties is required for freestanding Rh N clusters in a size range similar to that studied experimentally.…”
Section: Introductionmentioning
confidence: 93%
“…Several theoretical studies have shown that magnetism in 4d systems is strongly influenced by a number of factors, such as symmetry, coordination and interatomic distances. 17,21 One can expect that due to the large extension of the 4d wave functions the influence of atomic relaxations on magnetic moments of 4d systems should be stronger than for the 3d ones. We have performed spin-polarized and paramagnetic calculations for Pd and Rh chains of different sizes before the breaking in the relaxed geometry.…”
mentioning
confidence: 99%
“…be assigned to the second and third image state. In this way, besides the fact that the experimental and theoretical time scales are quite different, a direct comparison between our model calculations and corresponding experimental data, as for example published by Shumay et al, 46 is feasible.…”
Section: Ppe From Ag(100)mentioning
confidence: 75%